The Five Golden Rules of Negotiation - Korda, Philippe (Business Expert Press, 2011)
Ebook from IG Library ; Reveals the art of negotiation and helps you get the skills needed in becoming a master negotiator in today's business environment. The first part of the book outlines the fundamentals of negotiating, while the second part is devoted to getting the reader to understand their opponent's interests and tactics during the negotiation process. Finally, you get the opportunity to learn how to strategize successfully.